2010
DOI: 10.1371/journal.pone.0012240
|View full text |Cite
|
Sign up to set email alerts
|

When Ears Drive Hands: The Influence of Contact Sound on Reaching to Grasp

Abstract: BackgroundMost research on the roles of auditory information and its interaction with vision has focused on perceptual performance. Little is known on the effects of sound cues on visually-guided hand movements.Methodology/Principal FindingsWe recorded the sound produced by the fingers upon contact as participants grasped stimulus objects which were covered with different materials. Then, in a further session the pre-recorded contact sounds were delivered to participants via headphones before or following the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…When comparing this work with other research that showed how texture sounds can affect motor behavior (Castiello et al, 2010), it should be considered that, differently from those experiments, here the sound (and vibratory) feedback signals have always been congruent with the visual stimulus. It is possible that, if playing with incongruent sound feedback, significant behavioral differences would have been registered.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…When comparing this work with other research that showed how texture sounds can affect motor behavior (Castiello et al, 2010), it should be considered that, differently from those experiments, here the sound (and vibratory) feedback signals have always been congruent with the visual stimulus. It is possible that, if playing with incongruent sound feedback, significant behavioral differences would have been registered.…”
Section: Discussionmentioning
confidence: 76%
“…Castiello et al (2010) showed that the sound of fingers on different material textures affects movement duration in a reaching-to-grasp task, with sounds that are congruent with the visual appearance producing shorter movement durations. Moreover, their experiments provided evidence that the contact sound is used by both the planning and the on-line control systems at the neural level.…”
Section: Sound Out Of Texture Explorationmentioning
confidence: 99%
“…For these selfgenerated actions, there appears to be a predictive element to action-outcome temporal binding: as long as the probability of a sensory outcome is sufficiently high, the timing of a voluntary action will be pulled toward that expected outcome's position in time, even if the outcome does not occur (Moore & Haggard, 2008). In addition to influencing the perceived timing of actions and their outcomes, research has indicated that congruency between auditory and visual information can also influence the actual speed of motor actions (Castiello, Giordano, Begliomini, Ansuini, & Grassi, 2010).…”
Section: Future Directions: Multisensory Action Perceptionmentioning
confidence: 99%
“…sounds evoking a natural action on an object, were used (Aramaki & Kronland-Martinet, 2006;Conan et al, 2013;Thoret, Aramaki, Gondre, Kronland-Martinet, & Ystad, 2013). Indeed, the effectiveness of auditory FB strongly depends on the intuitive and correct interpretation of the applied mapping functions and metaphors (Castiello, Giordano, Begliomini, Ansuini, & Grassi, 2010).…”
Section: Movement Sonificationmentioning
confidence: 99%